A high-performance ambipolar organic field-effect transistor based on a bidirectional π-extended diketopyrrolopyrrole under ambient conditions1. Issue 66 (19th July 2015) - Bai, Jinfeng; Liu, Yucun; Oh, Sangyoon; Lei, Wenwei; Yin, Bingzhu; Park, Sooyoung; Kan, Yuhe
<x xml:space="preserve">Abstract</x> We reported a novel bidirectional π-extended DPP-2T2P–2DCV as an ambipolar semiconductor for high-performance and air-stable OFETs, exhibiting electron and hole mobilities of 0.168 cm2 V−1 s−1 and 0.015 cm2 V−1 s−1.